“Merayakan 125K Followers Instagram”: Studi atas Motivasi, Kreasi, dan Jangkauan sampai Juli 2026 - Wahyudin Darmalaksana (Gunung Djati Conference Series, 2026)
This article aims to analyze the growth of Instagram accounts. This research uses a qualitative approach by applying content analysis methods. The results of research and discussion show that Instagram account growth depends on creation, interaction and reach, but it begins with motivation. The conclusion of this research is that motivation precedes the growth of an Instagram account.